Synthesis, crystal structure and in vitro anticancer studies of two bis(8-quinolinolato-N,O)-platinum(II) complexes - Chen, Hong; Liu, Mingguo (European Journal of Chemistry, 2019)
Two bis(8-quinolinolato-N,O)-platinum(II) complexes, C18H12N2O2Pt (1) and C20H16N2O2Pt (2), were synthesized and characterized by FT-IR, elementary analysis and X-ray single crystal diffraction. Complex 1 crystallizes in monoclinic, space group P21/c with a = 9.3413(7), b = 10.3893(9), c = 14.8495(12) Å, β = 100.574(7)°, V = 1416.7(2) Å3. Complex 2 crystallizes in monoclinic, space group P21/n with a = 9.5115(11), b = 15.5692(18), c = 16.720(2) Å, β = 94.544(2)°, V = 2468.3(5) Å3. Intermolecular C-H···O hydrogen bonding interactions, as well as Pt···Pt and π-π stacking interactions, help to stabilize the crystal structures. The preliminary in vitro anticancer activity of complexes 1 and 2 and the corresponding ligands (L1 and L2) were investigated using human cervical (Hela) and hepatocellular carcinoma (Hep-G2) cancer cell lines. The platinum(II) complexes can greatly inhibit the cell proliferation and show stronger cytotoxic activities against the tested cancer cell lines than both ligands.